Leksikon Makanan Batalam Tradisi Maulid Di Bangkiling Raya dalam Perspektif Etnolinguistik - Rahmariani Rahmariani; Rusma Noortyani; Noor Eka Chandra (Universitas Lambung Mangkurat, 2026)
This study aims to identify and describe the lexical items used in the Maulid Batalam tradition in Bangkiling Raya Village, Banua Lawas District, Tabalong Regency, South Kalimantan. The Batalam tradition represents a unique form of Banjar local wisdom that integrates religious rituals and communal dining in a large shared platter called talam. This lexical study is crucial because the vocabulary embedded in this tradition remains under-documented despite its linguistic, cultural, and social value. This research employs a qualitative approach with descriptive ethnographic methods. Data were collected through direct observation, in-depth interviews with community figures and event organizers, and audiovisual documentation. The data were analyzed using data reduction, categorization, and verification techniques based on the Miles and Huberman model. The findings reveal that the core food lexicon, such as itik panggang (roasted duck), kuah sup (soup broth), and mi bahati (spiced duck liver noodles), are structured as noun phrases and carry significant lexical and cultural meanings. In addition, dozens of supporting lexical items were identified, covering aspects such as time, tools, places, and preparation processes. Cultural values such as kinship, cooperation, hospitality, and deliberation are reflected in the lexical choices. This study concludes that documenting local culinary lexicons contributes significantly to preserving the Banjar language and cultural identity in the face of increasing cultural homogenization.